1986
DOI: 10.1152/jappl.1986.61.6.2081
|View full text |Cite
|
Sign up to set email alerts
|

Late pulmonary responses induced by Ascaris allergen in conscious squirrel monkeys

Abstract: This study presents an antigen-dependent model of biphasic pulmonary changes to Ascaris suum in conscious squirrel monkeys. Animals with strong positive skin reactivity towards A. suum were trained to sit quietly in chairs and to breathe through face masks. Dynamic compliance (Cdyn) and pulmonary resistance (RL) were measured in these conscious animals before and for a period of 11 h after administration of an aerosol of Ascaris or ragweed antigen. The aerosol of Ascaris antigen induced reproducible increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Results of challenge with Ascaris antigen indicated that pulmonary changes occurred in the absence of any significant variations in f or VT [58]. Late responses occurred in four of nine animals which demonstrated early reactions.…”
Section: Nonhuman Primatesmentioning
confidence: 91%
See 2 more Smart Citations
“…Results of challenge with Ascaris antigen indicated that pulmonary changes occurred in the absence of any significant variations in f or VT [58]. Late responses occurred in four of nine animals which demonstrated early reactions.…”
Section: Nonhuman Primatesmentioning
confidence: 91%
“…Naturally sensitized, conscious squirrel monkeys have demonstrated immediate and late-phase responses upon aerosol challenge with Ascaris antigen [58]. Aerosol challenge was given through a face mask for a 6 min period.…”
Section: Nonhuman Primatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRFK-5 hybridoma was purchased from American Type Culture Collection (Rockville, Maryland, USA), grown in ascites fluid, and the antibody was partially purified by ammonium sulfate precipitation. In some experiments, anesthetized mice were exposed to nine doses (25 µl) of intranasal Ascaris pseudocoelomic fluid (APF; a kind gift of Joseph Urban, US Department of Agriculture, Bellville, Maryland, USA, and Fred Finkelman, University of Cincinnati, Cincinnati, Ohio, USA) (23)(24)(25)(26) on alternate days and analyzed 18 hours after the last allergen challenge. In other experiments, mice were sensitized by intraperitoneal injection of 50 µg of ovalbumin (OVA) and 1 mg alum in 0.9% sterile saline on two occasions separated by 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary hypersensitivity to exogenous antigen has been studied in the squirrel monkey ( Saimiri sciureus [1]), rhesus monkey ( Macaca mulatta [2]), Japanese monkey ( Macaca fuscata [3]) and cynomolgus monkey ( Macaca fascicularis [4]). The most common antigen used is an extract of Ascaris suum because a high percentage of these species of nonhuman primates show a natural hypersensitivity to this antigen.…”
Section: Introductionmentioning
confidence: 99%